PENGEMBANGAN MEDIA PEMBELAJARAN IPS SD tentang GEJALA ALAM MELALUI VIDEO ANIMASI - Sari, Kurnia Ratna (LPPM STKIP PGRI Bandar Lampung, 2019)
This study aims to develop social studies learning media in elementary schools about nature rehearsals through animated videos. The method used in this research is Research and Development (R&D). Based on the research results, it can be concluded that the use of multimedia-based learning media has a positive impact in supporting efforts to improve social studies learning outcomes.